PREDICTING THE DEVELOPMENT OF THROMBOTIC MICROANGIOPATHY IN PREGNANCY BASED ON CLINICAL AND GENETIC FACTORS: A CRITICAL REVIEW AND FUTURE PERSPECTIVES - Radjabova Zulola Abdukhakimovna (Journal Park Publishing, 2023)
Thrombotic microangiopathies (TMAs) of pregnancy, including severe preeclampsia (PE) and its critical form, HELLP syndrome, remain leading causes of maternal and perinatal mortality, as well as long-term cardiovascular complications. Their fulminant course necessitates the development of highly accurate predictive methods. This review systematizes current scientific data on the clinical and genetic predictors of severe forms of PE. Key pathogenetic mechanisms are examined, including the imbalance of angiogenic factors (sFlt-1/PlGF), oxidative stress, immune maladaptation, and microangiopathic hemolysis. The predictive value of clinical factors, biochemical markers, and genetic polymorphisms is analyzed. Special attention is given to genes controlling vascular tone (AGTR1, eNOS), angiogenesis (FLT1), and the hemostatic system (F5, SERPINE1). The principles of constructing and the limitations of existing integrative models are discussed. It is emphasized that a personalized approach is key to the timely initiation of preventive measures, intensification of monitoring, and selection of the optimal timing for delivery.
Keywords: Thrombotic microangiopathy, severe preeclampsia, HELLP syndrome, prediction, clinical factors, genetic predictors, sFlt-1/PlGF, endothelial dysfunction, microangiopathic hemolysis, polygenic risk, personalized medicine.